1990
DOI: 10.1111/j.1399-302x.1990.tb00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of streptococci of the “mutans” group to type 1 collagen associated with apatitic surfaces

Abstract: The present study surveyed the ability of 21 strains of cariogenic streptococci of the "mutans" group to bind to human type 1 collagen adsorbed on hydroxyapatite (HA) surfaces. All strains of Streptococcus cricetus (serotype a) and Streptococcus rattus (serotype b) tested attached strongly to collagen-treated HA (C-HA). Streptococcus mutans strains of serotype c and Streptococcus sobrinus strains of serotype d or g attached poorly; or not at all, to C-HA. S. mutans strains OMZ-175 (serotype f) and B14 (serotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Non-specific binding of P. intermedia to collagen must be ruled out because (i) no attachment of bacteria to BSAcoated wells was detected and (ii) complete inhibition of attachment occurred in the presence of free soluble collagen or its denatured form (gelatin). Collagen-binding capacity has been previously demonstrated for other oral bacterial species, including certain streptococci of the mutans group (Liu & Gibbons, 1990), Actinomyces viscos~s (Liu e t al., 1991) and Por. gingivalis (Naito & Gibbons, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Non-specific binding of P. intermedia to collagen must be ruled out because (i) no attachment of bacteria to BSAcoated wells was detected and (ii) complete inhibition of attachment occurred in the presence of free soluble collagen or its denatured form (gelatin). Collagen-binding capacity has been previously demonstrated for other oral bacterial species, including certain streptococci of the mutans group (Liu & Gibbons, 1990), Actinomyces viscos~s (Liu e t al., 1991) and Por. gingivalis (Naito & Gibbons, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…In the presence of an adherencepromoting component which may be provided from food, other organism, and so on, S. mutans can easily achieve initial adherence to the teeth. We previously reported that the supernatant of P. gingivalis ATCC Col-HA surface to mimic the matrices of dentin and cementum (17). Therefore, these findings suggest that the adherence of S. mutans to dentin and cementum of teeth in vivo may be increased by the vesicle.…”
mentioning
confidence: 80%
“…Adhesion to rat collagen type I and to human collagen types I and IV was not significant for either the wild type or the isogenic mutant IB08981 ( Table 1). As S. mutans OMZ 175 has been shown to bind to human collagen (28), this strain was included as a control. Compared with the wild type, adherence of the mutant to human fibronectin was reduced by 75% and to human laminin by 35% (Table 1).…”
Section: Resultsmentioning
confidence: 99%